Reconstructible pairs of incomplete polyhedral line drawings under general reconstruction procedure - Ishikawa, S.; Kato, K. (Pattern Recognition, 9th International Conference on, 1988: Proceedings, 2003)
A necessary and sufficient condition is described for a polyhedron to be reconstructed from its incomplete line drawings pair obtained from a stereo vision system. A practical judgement procedure using this condition is presented and the amount of knowledge that should be prepared for the judgement is also demonstrated experimentally.< >